2018
DOI: 10.1108/lodj-06-2018-0203
|View full text |Cite
|
Sign up to set email alerts
|

Destructive forms of leadership

Abstract: Purpose The purpose of this paper is to examine the relationship between abusive supervision and employee health and safety outcomes in Study 1 and to examine the effect of inconsistent leadership, operationalized as the interaction between transformational leadership and supervisor incivility, on employee safety participation in Study 2. Design/methodology/approach In Study 1, survey data were gathered from n=145 healthcare workers. In Study 2, survey data were gathered from n=177 nurses. Findings A parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 81 publications
4
27
0
Order By: Relevance
“…Moreover, as research of Mathieu and Babiak (2015) has shown, negative leadership styles and behaviours, as opposed to positive ones, have a more substantial impact on employee attitudes. Several studies examined the dimensionality of such destructive forms of leadership (e.g., Mitchell and Ambrose, 2007;Valle et al, 2019), identifying their antecedents and consequences (Mullen et al, 2018;Tepper, 2000;Tepper et al, 2009), and to a lesser extent, proposing theoretical models explaining the nature of such leadership (Einarsen et al, 2007;Krasikova et al, 2013;Thoroughgood et al, 2018;Wang et al, 2010). Still, although research on these forms of leadership has grown in the past few years, it is plagued with three problems:…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as research of Mathieu and Babiak (2015) has shown, negative leadership styles and behaviours, as opposed to positive ones, have a more substantial impact on employee attitudes. Several studies examined the dimensionality of such destructive forms of leadership (e.g., Mitchell and Ambrose, 2007;Valle et al, 2019), identifying their antecedents and consequences (Mullen et al, 2018;Tepper, 2000;Tepper et al, 2009), and to a lesser extent, proposing theoretical models explaining the nature of such leadership (Einarsen et al, 2007;Krasikova et al, 2013;Thoroughgood et al, 2018;Wang et al, 2010). Still, although research on these forms of leadership has grown in the past few years, it is plagued with three problems:…”
Section: Introductionmentioning
confidence: 99%
“…, 2018), while it can also have a negative indirect effect through lowering their internal identity perceptions. Although previous research indicated such negative correlation between SI and psychological safety (Mullen et al. , 2018; Smittick et al.…”
Section: Discussionmentioning
confidence: 83%
“…Antecedents of psychological safety include proactive personality, disposition of a person to feel calm and relaxed, as well as supportive relationships, peer and leader support (Mullen et al. , 2018; Khan, 2021).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a high enthusiasm at work 6. Having high quality to get the job done Mullen, Fiset, and Rhéaume (2018) showed significant results between destructive leadership and employee performance. The study revealed that employee mental health disorders caused by destructive leadership affected employee performance.…”
Section: Sutrisno Teofilus Silaswara and Rusmimentioning
confidence: 99%